Pengaruh Pendapatan, Tingkat Pendidikan, dan Investasi Terhadap Tingkat Literasi Keuangan pada Pelaku UMKM (Studi Kasus UMKM di Kecamatan Juwana Kabupaten Pati) - Ulfah Kholishotul Muna Mas’adah; Ernawati Budi Astuti (AKSES: Jurnal Ekonomi dan Bisnis, 2022)
The study aims to determine the influence of income, education level, and investment on financial literacy in MSME actors in Juwana District, Pati Regency. The study used a descriptive quantitative method with data collection techniques using questionnaires with a total sample of 97 MSME respondents in Juwana District, Pati Regency with spss statistical tool version 26. Data analysis used validity test, reability test, classical assumption test, multiple linear regression analysis, t test, F test, determinant coefficient.. The results of the study based on partial tests (t tests) (1) income variables obtained calculated t values of 3.078 > t table 1.985 and sighnifikansi values (Sig) 0.03 < 0.05 (2) education level variables obtained calculated t values 12.914 > t table 1.985 and sighnifikansi values (Sig) 0.00 < 0.05 (3) investment variables obtained calculated t values 17.555 > t table 1.985 and sighnifikansi values (Sig) 0.000 < 0.05, so that the results obtained have an influence between the variables of income, level of education and investment on financial literacy. Simultaneous results (F-tests) of the variables of education, level of education, and investment showed an effect on financial literacy. The results of the determinant coefficient test showed the influence of income, education level, and investment on financial literacy by 92.6% and the remaining 7.4% was influenced by other variables that were not present in this study.